Respiratory Syncytial Virus Glycoprotein G Interacts with DC-SIGN and L-SIGN To Activate ERK1 and ERK2 - Johnson, Teresa R. (American Society for Microbiology, 2012)
Respiratory syncytial virus (RSV) interaction with epithelial and dendritic cells (DCs) is known to require divalent cations, suggesting involvement of C-type lectins. RSV infection and maturation of primary human DCs are reduced in a dose-dependent manner by EDTA. Therefore, we asked whether RSV infection involves DC-SIGN (CD209) or its isoform L-SIGN (CD299) (DC-SIGN/R). Using surface plasmon resonance analysis, we demonstrated that the attachment G glycoprotein of RSV binds both DC- and L-SIGN. However, neutralization of DC- and L-SIGN on primary human DCs did not inhibit RSV infection, demonstrating that interactions between RSV G and DC- or L-SIGN are not required for productive infection. Thus, neither DC- nor L-SIGN represents a functional receptor for RSV. However, inhibition of these interactions increased DC activation, as evidenced by significantly higher levels of alpha interferon (IFN-α), MIP-1α, and MIP-1β in plasmacytoid DCs (pDCs) exposed to RSV after neutralization of DC-and L-SIGN. To understand the molecular interactions involved, intracellular signaling events triggered by purified RSV G glycoprotein were examined in DC- and L-SIGN-transfected 3T3 cells. RSV G interaction with DC- or L-SIGN was shown to stimulate ERK1 and ERK2 phosphorylation, with statistically significant increases relative to mock-infected cells. Neutralization of DC- and L-SIGN reduced ERK1/2 phosphorylation. With increased DC activation following DC- and L-SIGN neutralization and RSV exposure, these data demonstrate that the signaling events mediated by RSV G interactions with DC/L-SIGN are immunomodulatory and diminish DC activation, which may limit induction of RSV-specific immunity.